Phylogeny, ethnomedicinal use and the distribution of phytoestrogens in the Fabaceae - Thaweepanyaporn, Kongkidakorn; Thompson, Jamie B.; Vasudevan, Nandini; Hawkins, Julie A. (Frontiers in Pharmacology, 2025)
IntroductionPhytoestrogens, with estrogenic activity, are commonly found across the Fabaceae family. Here we develop methods that use phylogeny and ethnomedicinal information in order to identify candidate species for novel phytoestrogens.MethodWe selected Fabaceae species traditionally used as aphrodisiacs or with applications to control fertility (aphrodisiac-fertility species), to create a cross-cultural dataset of ethnomedicinal use. Using a phylogeny of the Fabaceae, “hot nodes” methods were used to identify lineages with a higher number of species with aphrodisiac-fertility uses. The known distribution of estrogenic flavonoids was used to determine whether the phytoestrogen-containing species was associated with aphrodisiac-fertility “hot nodes”. Additionally, we examined the overlap of aphrodisiac-fertility uses with neurological applications, hypothesising that such species may have bioactive compounds with estrogenic properties. Lastly, the “aphrodisiac-fertility hot node” lineages without previously known estrogenic flavonoids were identified.ResultsWe showed species in aphrodisiac-fertility hot nodes were more likely to contain estrogenic flavonoids (21% of species), a major group of phytoestrogens, compared to Fabaceae in the phylogeny (11% of species). Additionally, when aphrodisiac fertility species are limited to those with neurological applications, 62% of the species within hot nodes contain estrogenic flavonoids.DiscussionWe recognised 43 high-priority hot nodes, these lineages might represent promising targets for future studies on phytoestrogens. The results demonstrated the combining phylogenetic and ethnomedicinal data to guide the discovery of estrogenic flavonoids with therapeutic potential.